719 CIRCULATING SORTILIN LEVELS ARE INCREASED IN PATIENTS RECEIVING LONG-TERM WARFARIN AND ITS INHIBITION ATTENUATES WARFARIN-INDUCED VASCULAR CALCIFICATION. (15th December 2022) - Di Pietro, Paola; Abate, Angela Carmelita; Rusciano, Maria Rosaria; Visco, Valeria; Izzo, Carmine; Iacoviello, Licia; Toni, Anna Laura; Ciccarelli, Michele; Carrizzo, Albino; Vecchione, Carmine
Abstract: Long-term use of the vitamin K antagonist (VKA) warfarin, has been shown to accelerate vascular and valvular calcification both in rodents and in humans. Increasing evidence suggests that vascular endothelium contributes to calcification via endothelial-mesenchymal transition (EndMT). However, additional research is warranted to elucidate the signaling mechanisms involved. In the last decade, a prominent role for sortilin has been demonstrated in cardiovascular calcification. Moreover, we recently demonstrated that the increase of sortilin in the endothelium promotes endothelial dysfunction, a known initiator of EndMT. Thus, we aim to investigate a potential contribution of sortilin in vascular calcification induced by warfarin. For this purpose, human endothelial cells and aortic rings from wild type C57BL/6J mice were cultured in promineralization medium in the presence of therapeutic levels of warfarin. Plasma sortilin and calcium levels were measured in 19 patients under VKA therapy who were stratified into short-term (3-12 months) or long-term group (24-45 months) based on VKA treatment duration. Increased protein expression of sortilin was found both in the endothelial and in the medial smooth muscle layers of aortic rings. Sortilin immunostaining was found to co-localize with α-SMA in the endothelium of warfarin-treated aortic rings, a hallmark of EndMT. Interestingly, pharmacological inhibition of sortilin with AF38469 reduced calcification and prevented loss of expression of the endothelial marker von Willebrand Factor (vWF) induced by warfarin treatment in human endothelial cells and mouse aortas. Finally, along with elevated plasma calcium levels, patients receiving long-term VKA showed increased circulating sortilin levels when compared to short term VKA-treated patients. Our data provide evidence for a potential role for endothelial-derived sortilin in regulating vascular calcification promoted by warfarin, and suggest that targeting circulating sortilin may be beneficial for the prevention of warfarin-associated cardiovascular calcification.